Business research methods - Cooper, Donald R.; Schindler, Pamela S. (New York : McGraw Hill Education, 2014)
Our book is designed for a one-semester course although under no circumstances is it imagined that the entire book be covered.
Part I : Introduction to business research -- Part II : The Design of business research -- Part III : The Sources and collection of data -- Part IV : Analysis and presentation of data
Includes bibliographical references and index.
Keywords: BUSINESS -- RESEARCH -- METHODOLOGY